Dramatic conflict in the drama "The Lonely" by G. Hauptmann (Literatures of the World: Poetics, Mentality and Spirituality, 2015)
The attempt is made to analyse the structure of dramatic conflict in the drama “Lonely People” of G. Hauptmann in the article. The peculiarities of character creating and problem of genre originality are studied through the prism of texts of naturalistic drama. Permanent features of playwrights’ poetics, the immanent structure of the conflict design, its content dominating ideas and determining features are studied. At the same time the article provides insights into the aesthetic and philosophical evolution of the playwright’s literary thinking.
Keywords: dramatic conflict; German drama; genre and style peculiarities; literary thinking